2011
DOI: 10.3109/10673229.2011.614483
|View full text |Cite
|
Sign up to set email alerts
|

The Psychopharmacology Algorithm Project at the Harvard South Shore Program: An Update on Posttraumatic Stress Disorder

Abstract: This heuristic may be helpful in producing faster symptom resolution, fewer side effects, and increased compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 111 publications
0
39
0
Order By: Relevance
“…Upcoming results from 2 large clinical trials of use of prazosin to treat PTSD symptoms (a 13-site VA study of 320 veterans and a single-site study of 120 soldiers on active duty), expected to be completed in late 2012, will add greatly to our knowledge. 38 There are several limitations to the present literature review. One is the relatively small number of studies and total number of patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Upcoming results from 2 large clinical trials of use of prazosin to treat PTSD symptoms (a 13-site VA study of 320 veterans and a single-site study of 120 soldiers on active duty), expected to be completed in late 2012, will add greatly to our knowledge. 38 There are several limitations to the present literature review. One is the relatively small number of studies and total number of patients.…”
Section: Discussionmentioning
confidence: 91%
“…[38][39][40][41][42] We used a method that would be reproducible for future updates, and we assessed the risk of bias for the randomized studies. Already, our review includes 2 recent studies from 2010 and 2012 that other recent reviews were unable to include, and the significance is that one of these studies reported a negative finding and the other study reported less impressive results than the earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…This algorithm update is one of several recently published by the PAPHSS (1,(8)(9)(10)(11) and available in condensed format for access on smart phone devices on the website www.psychopharm.mobi. The methods of producing these algorithms have been described in the previous publications.…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons it is useful to treat insomnia first. 22 Sleep disturbances in PTSD are thought to be related to hyperarousal and increased adrenergic activity, which may lead to related symptoms such as nightmares, difficulty initiating sleep, and frequent awakenings. Two medications that decrease nightmares and improve sleep quality are prazosin, and trazodone.…”
Section: Preferred Pharmacologic Management Of Ptsd Symptoms Sleepmentioning
confidence: 99%